(untitled) (Principles and Practice of Clinical Research, 2021)
Background: The discovery of the COVID-19 virus and the subsequent rapid pandemic has had a significant impact not only on public health but also on clinical education. Continuing Professional Development (CPD) within the Primary Health Care Corporation (PHCC) had to be adapted, especially regarding the methods of delivery. Social distancing was a requirement from the Public Health directives, impacting the practicalities of face-to-face didactic and simulated clinical educational sessions. Given the challenges that the pandemic generated across the globe in terms of education, new ways of offering education were required as a matter of urgency. This evaluative study was undertaken to describe the PHCC Workforce Training and Development’s (WTD) response to achieve maximum efficacy of our delivered CPD. Methods: The purpose of this descriptive study was to explore the interventions utilized by the WTD directorate within PHCC. The evaluation and comparison of teaching and learning interventions (in terms of subject matter and delivery method) were described. It was based upon a three-month period from pre-COVID-19 (2019) and mid-COVID19 (2020). Staff who attend CPD programs within PHCC included: Physicians, Nurses, Dentists, and allied health care professionals. Results: During a three-month period from the pre-COVID-19 year (2019), 68 CPD courses were delivered mainly face-to-face, and individual accreditation varied from 1 to 30.25 educational accreditation points. During the mid-COVID year (2020), 38 CPD courses were delivered as online webinars and individual accreditation varied from 1 to 3.75 educational accreditation points. It was found that a greater number of participants were able to undertake web-based learning with individual sessions than face-to-face ones. Microsoft Teams was successfully utilized. The remote online host lecturer has facilitated significant interaction with most participants. The lecturers received the Learning Management System (LMS) training prior to the Pandemic; thus, we have experienced an easier integration of ongoing online clinical education during these challenging times. Conclusion: It was acknowledged that the WTD directorate at PHCC was in a fortunate position, due to the integration of the online LMS training prior to the pandemic. Both the clinical and educational staff were able to implement and deliver this method effectively at short notice, with similar academic accredited standards and quality. It is expected that following the pandemic, a higher uptake, demand, and motivation for innovative learning approaches will occur. It is thought that the use of the blended learning approach will dramatically increase.